Pre-electoral coalitions and the distribution of political power - Hortala‑Vallve Rafael; Meriläinen Jaakko; Tukiainen Janne (Springer (commercial publisher), 2025)
Pre-electoral coalitions (PECs) may increase parties’ chances of winning an election, but they may also distort electoral results and policies away from citizens’ preferences. To shed light on how PECs shape post-electoral power distribution, we study the causes and consequences of PECs in Finland where elections use an open-list proportional representation system, and parties may form joint lists. We present descriptive evidence showing that PECs are more common between parties of equal size and similar ideology, and when elections are more disproportional or involve more parties. Using diference-indiferences and density discontinuity designs, we illustrate that voters punish coalescing parties and target personal votes strategically within the coalitions, and that PECs are formed with the particular purpose of infuencing the distribution of power. PECs increase small parties’ chances of acquiring leadership positions, lead to more dispersed seat distributions, and sometimes prevent absolute majorities. They can thus enable a broader representation of citizens’ policy preferences.